The Evolutionary Dynamics of the Mitochondrial tRNA in the Cichlid Fish Family - Yosur G. Fiteha; Mahmoud Magdy (Biology, 2022)
The mitochondrial transfer RNA genes (tRNAs) attract more attention due to their highly dynamic and rapidly evolving nature. The current study aimed to detect and evaluate the dynamics, characteristic patterns, and variations of mitochondrial tRNAs. The study was conducted in two main parts: first, the published mitogenomic sequences of cichlids mt tRNAs have been filtered. Second, the filtered mitochondrial tRNA and additional new mitogenomes representing the most prevalent Egyptian tilapiine were compared and analyzed. Our results revealed that all 22 tRNAs of cichlids folded into a classical cloverleaf secondary structure with four domains, except for trnSGCU, missing the D domain in all cichlids. When consensus tRNAs were compared, most of the mutations were observed in the trnP at nucleotide levels (substitutions and indels), in contrast to trnLUAA. From a structural perspective, the anticodon loop and T-loop formations were the most conserved structures among all parts of the tRNA in contrast to the A-stem and D-loop formations. The trnW was the lowest polymorphic unneutral tRNA among all cichlids (both the family and the haplotilapiine lineage), in contrast with the neutral trnD that was extremely polymorphic among and within the haplotilapiine lineage species compared to other cichlids species. From a phylogenetic perspective, the trnC was extremely hypervariable and neutral tRNA in both haplotilapiine lineage and cichlids but was unable to report correct phylogenetic signal for the cichlids. In contrast to trnI and trnY, less variable neutral tRNAs that were able to cluster the haplotilapiine lineage and cichlids species as previously reported. By observing the DNA polymorphism in the coding DNA sequences (CDS), the highest affected amino acid by non-synonymous mutations was isoleucine and was equally mutated to valine and vice versa; no correlation between mutations in CDS and tRNAs was statistically found. The current study provides an insight into the mitochondrial tRNA evolution and its effect on the cichlid diversity and speciation model at the maternal level.